Immune Regulation and ECM-Related Pathway Enrichment Reveal ATP2A3 as a Prognostic Biomarker for Nonspecific Orbital Inflammation: An Integrated Machine Learning and Mendelian Randomization Analysis - Zixuan Wu; Xi Long; Kang Tan; Xiaolei Yao; Qinghua Peng (Mediators of Inflammation)
Conclusions: In the context of NSOI, we identify ATP2A3 as a novel contributor to immune-driven pathogenesis. Its significant dysregulation in NSOI tissues relative to healthy controls underscores its potential as a prognostic marker within the inflammatory microenvironment.